Prevalence and risk factors for pelvic organ prolapse 20 years after childbirth: a national cohort study in singleton primiparae after vaginal or caesarean delivery. (2nd November 2012) - Gyhagen, M; Bullarbo, M; Nielsen, TF; Milsom, I
Abstract : Please cite this paper as: Gyhagen M, Bullarbo M, Nielsen T, Milsom I. Prevalence and risk factors for pelvic organ prolapse 20 years after childbirth: a national cohort study in singleton primiparae after vaginal or caesarean delivery. BJOG 2012; DOI : 10.1111/1471‐0528.12020. Objective  To investigate prevalence and risk factors for symptomatic pelvic organ prolapse (sPOP) and sPOP concomitant with urinary incontinence (UI) in women 20 years after one vaginal delivery or one caesarean delivery. Design  Registry‐based national cohort study. Setting  Women who returned a postal questionnaire in 2008 (response rate 65.2%). Population  Singleton primiparae with a birth in 1985–88 and no further births ( n  = 5236). Methods  The SWEPOP study used validated questionnaires about sPOP and UI. Main outcome measures  Prevalence rate and risk of sPOP with or without concomitant UI. Results  Prevalence of sPOP was higher after vaginal delivery compared with caesarean section (14.6 versus 6.3%, odds ratio [OR] 2.55; 95% confidence interval [95% CI] 1.98–3.28) but was not increased after acute compared with elective caesarean section. Episiotomy, vacuum extraction and second‐degree or more laceration were not associated with increased risk of sPOP compared with spontaneous vaginal delivery. Symptomatic POP increased 3% (OR 1.03; 95% CI 1.01–1.05) with each unit increase of current BMI and by 3% (OR 1.03; 95% CI 1.02–1.05) for each 100 g increase of infant birthweight. Mothers ≤160 cm who delivered a child with birthweight ≥4000 g had a doubled prevalence of sPOP compared with short mothers who delivered an infant weighing <4000 g (24.2 versus 13.4%, OR 2.06; 95% CI 1.19–3.55). Women with sPOP had UI and UI > 10 years more often than women without prolapse. Conclusion  The prevalence of sPOP was doubled after vaginal delivery compared with caesarean section, two decades after one birth. Infant birthweight and current BMI were risk factors for sPOP after vaginal delivery.